2007
DOI: 10.1038/modpathol.3800735
|View full text |Cite
|
Sign up to set email alerts
|

IMP3 is a novel biomarker for adenocarcinoma in situ of the uterine cervix: an immunohistochemical study in comparison with p16INK4a expression

Abstract: Adenocarcinoma in situ of the uterine cervix remains a diagnostic challenge in a small proportion of cases. This suggests a need for biomarker that may be of help in establishing the diagnosis. The aim of this study was to evaluate the potential of insulin-like growth factor-II mRNA-binding protein 3 and cyclin-dependent kinase inhibitor p16 INK4a as biomarkers for adenocarcinoma in situ. Forty-four samples of adenocarcinoma in situ from 40 patients and 23 control cases of benign uterine cervix were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 21 publications
5
83
0
Order By: Relevance
“…Although IGF2BP3 is expressed in a variety of malignant neoplasms, including pulmonary small cell, 19 endometrial, 20 and cervical carcinomas, 21 prognostic value has been shown only in renal clear cell carcinomas, 8 other types of renal carcinomas, 22 and low-stage urothelial carcinomas of the bladder. 23 Validation of the association with prognosis in an independent case series has been exclusively reported for renal clear cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IGF2BP3 is expressed in a variety of malignant neoplasms, including pulmonary small cell, 19 endometrial, 20 and cervical carcinomas, 21 prognostic value has been shown only in renal clear cell carcinomas, 8 other types of renal carcinomas, 22 and low-stage urothelial carcinomas of the bladder. 23 Validation of the association with prognosis in an independent case series has been exclusively reported for renal clear cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray hybridization and washing were carried out using standard procedures. 20,21 Microarrays were scanned on a GenePix 4000 microarray scanner and fluorescence ratios (tumor/reference) were calculated using GenePix software. Only spots with a ratio of signal over background of at least 1.5 in the Cy5 and 1.5 in the Cy3 channel were included.…”
Section: Antibody Confirmationmentioning
confidence: 99%
“…A monoclonal antibody specific for IMP3 has been developed and used successfully with routine immunohistochemical methods to study overexpression of the protein in malignant pancreatic, renal, and uterine endocervical lesions. 3,7,8 Expression of IMP3 in endometrial carcinomas has not been previously studied. The aims of this study were to evaluate the expression of IMP3 in endometrial carcinomas especially endometrioid adenocarcinoma and serous carcinoma subtypes as well as benign endometrium using immunohistochemical techniques, to assess the diagnostic utility of IMP3 in distinguishing endometrioid adenocarcinoma from serous carcinoma, to correlate IMP3 expression with clinicopathologic features of the disease, and to understand the possible role of IMP3 in the pathogenesis of endometrial adenocarcinoma.…”
mentioning
confidence: 99%
“…Although IMP3 expression is normal in embryonic epithelium, muscle, and placenta of the human fetus, its expression is either minimal or absent in adult human tissues (8,10). This oncofetal protein is highly expressed in various types of human malignant neoplasm, including lung, colon, pancreas, and stomach cancers; soft tissue sarcomas; endometrial serous carcinoma; and endocervical adenocarcinoma; there is, however, no expression in the surrounding benign tissues (9,(11)(12)(13)(14)(15). Few studies have shown that IMP3 is a very useful marker to diagnose low-grade from high-grade Esophageal dysplasia/adenocarcinoma (5,16).…”
Section: Introductionmentioning
confidence: 99%